An update on the distribution, bionomics, and insecticide susceptibility of Anopheles stephensi in Ethiopia, 2018–2020 - Balkew, Meshesha (Malar J, 2021)
BACKGROUND: Anopheles stephensi, an invasive malaria vector, was first detected in Africa nearly 10 years ago. After the initial finding in Djibouti, it has subsequently been found in Ethiopia, Sudan and Somalia. To better inform policies and vector control decisions, it is important to understand the distribution, bionomics, insecticide susceptibility, and transmission potential of An. stephensi. These aspects were studied as part of routine entomological monitoring in Ethiopia between 2018 and 2020. METHODS: Adult mosquitoes were collected using human landing collections, pyrethrum spray catches, CDC light traps, animal-baited tent traps, resting boxes, and manual aspiration from animal shelters. Larvae were collected using hand-held dippers. The source of blood in blood-fed mosquitoes and the presence of sporozoites was assessed through enzyme-linked immunosorbent assays (ELISA). Insecticide susceptibility was assessed for pyrethroids, organophosphates and carbamates. RESULTS: Adult An. stephensi were collected with aspiration, black resting boxes, and animal-baited traps collecting the highest numbers of mosquitoes. Although sampling efforts were geographically widespread, An. stephensi larvae were collected in urban and rural sites in eastern Ethiopia, but An. stephensi larvae were not found in western Ethiopian sites. Blood-meal analysis revealed a high proportion of blood meals that were taken from goats, and only a small proportion from humans. Plasmodium vivax was detected in wild-collected An. stephensi. High levels of insecticide resistance were detected to pyrethroids, carbamates and organophosphates. Pre-exposure to piperonyl butoxide increased susceptibility to pyrethroids. Larvae were found to be susceptible to temephos. CONCLUSIONS: Understanding the bionomics, insecticide susceptibility and distribution of An. stephensi will improve the quality of a national response in Ethiopia and provide additional information on populations of this invasive species in Africa. Further work is needed to understand the role that An. stephensi will have in Plasmodium transmission and malaria case incidence. While additional data are being collected, national programmes can use the available data to formulate and operationalize national strategies against the threat of An. stephensi. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12936-021-03801-3.